2019
DOI: 10.1186/s13287-019-1140-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical micronization of lipoaspirates for the treatment of hypertrophic scars

Abstract: BackgroundHypertrophic scars cause cosmetic and functional problems for patients, and their treatment remains challenging. Mechanical micronization of adipose tissue can remove adipocytes and concentrate functional cells. Stromal vascular fraction (SVF)-gel is obtained by a series of simple mechanical processes, including shifting between syringes and centrifugation. This study aimed to assess the therapeutic effect of SVF-gel on hypertrophic scars.MethodsA model of hypertrophic scars was established in rabbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…Several studies have demonstrated the capacity of ADSCs to promote phenotype switching in macrophages, inhibiting expression of M1 polarization genes. Consistent with previous reports [28], SVF gel decreased macrophage in ltration and pro-in ammatory cytokines, indicative of decreased in ammation. Further, apoptotic adipose cells and skin lesion brosis were decreased in mice treated with SVF gel.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have demonstrated the capacity of ADSCs to promote phenotype switching in macrophages, inhibiting expression of M1 polarization genes. Consistent with previous reports [28], SVF gel decreased macrophage in ltration and pro-in ammatory cytokines, indicative of decreased in ammation. Further, apoptotic adipose cells and skin lesion brosis were decreased in mice treated with SVF gel.…”
Section: Discussionsupporting
confidence: 92%
“…Lipotransfer has already been explored as a therapeutic approach for reversing brosis in a number of brotic conditions [28]. In 2012, Ould-ali et al demonstrated that implantation of human adipose tissue signi cantly improved brosis in sclerotic skin lesions of the BLM-induced mouse model, suggesting autologous adipose tissue as a promising novel therapy for scleroderma [29].…”
Section: Discussionmentioning
confidence: 99%
“…The application of SVF gel and SVF cells reduced macrophage infiltration in the dermal layer as well as the expression of interleukin-6 mRNA and monocytic chemoattractive protein-1 (MCP-1). In addition, myofibroblast number and collagen formation were reduced in groups using SVF gel and SVF cells [49]. According to these and other researchers, the positive effect in the correction of scars is due to the secretion of various cytokines and growth factors by the progenitor cells of adipose tissue, including hepatocyte growth factor, IL-10 and adrenomedullin which have antifibrotic properties [24,29].…”
Section: Experimental Studies Of Adscs Application For Skin Lesionsmentioning
confidence: 85%
“…Hence, we postulated that the immunoregulatory capacity of ASCs differed between the 10 4 group and the 10 8 group. Given that the α-SMA level was the same as in the control group, the main function of ASCs in the 10 4 group might be to inhibit excessive secretion of extracellular matrix (ECM) proteins and promote degradation of ECM proteins [48]. In fact, there are several possible mechanisms of ASCs anti brotic effects, including the regulation of TGF-β/Smad axis, the paracrine mechanisms, the antioxidant effects of ASCs and so on [49].…”
Section: Discussionmentioning
confidence: 99%